Interventions to Ensure the Continuum of Care for Hypertension During the COVID-19 Pandemic in Five Indian States—India Hypertension Control Initiative. Issue 1 (8th December 2021) - Kunwar, Abhishek; Durgad, Kiran; Kaur, Prabhdeep; Sharma, Meenakshi; Swasticharan, Leimapokpam; Mallela, Madhavi; Saxena, Ashish; Tayade, Sadhana; Gill, Sandeep; Gopal, Bipin K.; Pathni, Anupam K.; Tullu, Fikru T.; et al.
Background: Hypertension is the leading risk factor for cardiovascular disease in India, but less than 10% of the estimated people with hypertension have blood pressure under control. The India Hypertension Control Initiative (IHCI) was implemented to strengthen hypertension management and control in public sector health facilities. Since late March 2020, lockdown due to the COVID-19 pandemic limited healthcare access and disrupted the provision of essential health services. IHCI quickly implemented adaptive interventions to improve access to medications. Objectives: To estimate the availability of antihypertensive drugs in peripheral public sector facilities during the lockdown and the proportion of patients who received drugs through community drug distribution, i.e., through Health and Wellness Centers (HWCs)/Sub-Centers (SCs), the most peripheral public sector health facilities for primary care, and home delivery. Methods: We collected data from 29 IHCI districts of 5 states (Kerala, Madhya Pradesh, Maharashtra, Punjab, and Telangana) during April–May 2020. The population included individuals diagnosed with hypertension and enrolled under IHCI in all public sector primary care health facilities. We contacted a convenience sample of more than one-third of the functional HWC/SC and analyzed the proportion of facilities and patients who received drugs. We also contacted a convenience sample of patients telephonically to estimate their self-reported availability of drugs. Conclusion: Of the 4245 HWC/SC, more than one-third were contacted telephonically, and 85–88% had received antihypertensive medications for community-level distribution. Among 721, 675 patients registered until March 2020, 38.4% had received drug refills through HWC/SC or home delivery by frontline workers during the lockdown. We demonstrated the feasibility of community-level drug distribution for patients with hypertension during the COVID-19 lockdown in India. The adaptive strategy of community-based drug distribution through HWC/SC and home delivery appears feasible and may help improve access to hypertension care during the COVID-19 pandemic and beyond.